(3ebOeI aj GdeGdjI GdOhdjIs - (3fhRGO YHO GdQMef(B, (3GdgjJjs; (3efLO YHO GddWja(B, (3GdNTGdjs ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2007)
(3eaghe GdeGdjI GdOhdjI hJWhQgG GdJGQjNj, ejRGf GdeOahYGJ Gdeaghe hBdjGJ GdJhGRf, GdefGgL GdfXQjI dJUMjM GdYLR aj ejRGf GdeOahYGJ, GdJZjQGJ aj CSYGQ UQa GdYedI hCKGQgG GdEbJUGOjI hGdELJeGYjI, GdQbGHI Ydi GdUQa GdCLfHj, MQcI QDhS GdCehGd GdOhdjI, GdefXeGJ GdeGdjI GdOhdjI hGdYQHjI,GdTQcGJ eJYOOI GdLfSjI COGI eMQcI ddYhdeI, GdeSGYOGJGdEfeGFjI GdOhdjI hCKGQgG GdEbJUGOjI hGdSjGSjI hGdELJeGYjIs
Keywords: (3GdfXGe GdfbOj GdOhdjs